ESTIMATE OF PARTICLE SIZE DISTRIBUTION GOLD KINETIC REACTIONS ULTRAFAST, USING LIGHT ABSORPTION SPECTRA - Briano, Julio (2007)
Light absorption spectra were used to estímate gold particles growing kinetics following a gold salt (HAuCl4) reduction by sulfite in aqueous solution. Due this process is extremely fast, e.g. part1cles reach 150nm s1ze in less a second, a special equipment denorninated Stopped Flow Reactor (AFR) was used. Light spectra was modeled using Mie theory for monodisperse particles with1n 30-250nm range size, and tor minor sizes experimental spectra of commercial colloids were used, due to uncertainly in dielectric constant for these sizes.Three different approaches were proposed to estimate the gold particles size distribution evolution, and experimental intensity and shape of spectra were used to validate the computation. The most simply approach considers the assumption that particles are compact spheres and monodisperse, following model of LaMer. A second approach is based on growth model of spherical and compact particles with binomial distribution for the sizes, and following mechanisms set by Matjicevic y Privman. The last approach is based in a monodisperse distribution of spherical particles with heterogeneous structure according to Bruggeman model. Each model has a good performance in matching calculation to data at different times, indicating, in this way, this growth kinetics follows complexes mechanisms, and the predominant one change as the process evolves.